2021
DOI: 10.1177/00368504211033708
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous sedation management for an outpatient with dental phobia and vasovagal reflex following an atrioventricular junctional rhythm: A case report

Abstract: Perioperative arrhythmias may be induced by an imbalance between sympathetic and parasympathetic activities owing to excessive mental and physical stress. To date, no studies have been conducted on intravenous sedation (IVS) during dental procedures in a serious dental anxiety patient with atrioventricular junctional rhythm (AVJR). We describe herein the management of IVS in an outpatient with dental phobia who experienced the AVJR followed by vasovagal reflex (VVR) during dental care. A 26-year-old woman with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…We need to distinguish and diagnose the electrocardiographic changes that suggest the possible signs associated with VVR such as AVJR 12 or asystole resulting from parasympathetic hypertonia owing to painful stress of venipuncture for peripheral intravenous catheterization or local anesthetic injection to oral mucosa. On the contrary, it is also reported that the cerebral hypoperfusion causes unconsciousness approximately 6 to 8 s after asystole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We need to distinguish and diagnose the electrocardiographic changes that suggest the possible signs associated with VVR such as AVJR 12 or asystole resulting from parasympathetic hypertonia owing to painful stress of venipuncture for peripheral intravenous catheterization or local anesthetic injection to oral mucosa. On the contrary, it is also reported that the cerebral hypoperfusion causes unconsciousness approximately 6 to 8 s after asystole.…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative general conditions such as hypovolemia due to dehydration, or anemia, which are involved in the systemic risk factors triggering cardiac events, should be recognized and improved before surgery. 3 Therefore, it is necessary to differentiate the underlying cardiovascular diseases as the possible causes of hemodynamic disorders or electrocardiographic changes including AVJR 12 or asystole.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5,7,8] Most dental and oral surgical procedures are performed under local anesthesia; therefore, failure to properly assess and control pain can lead to problems such as elevated blood pressure, vasovagal reflexes, and treatment interruptions. [14,15] For example, Gürler et al previously reported that acute dental pain can induce elevated stress hormone levels. [16] However, pain is difficult to assess as it is based on personal experiences influenced by biological, psychological, and social factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, during dental procedures with acute pain, blood pressure fluctuations and vasovagal reflexes may occur because of changes in the autonomic nervous system. [38,39] These conditions should be assessed and managed by dentists before, during, and after dental treatment. However, these are still important dental clinical problems because they are complex situations related to the subjective psychological state of the patient and acute dental pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, these are still important dental clinical problems because they are complex situations related to the subjective psychological state of the patient and acute dental pain. [38,39] In light of this point of view, the authors listed and discussed the current status and issues in the development of acute dental pain assessment methods.…”
Section: Discussionmentioning
confidence: 99%